Hydrogeochemical Characteristics and Formation of Low-Temperature Geothermal Waters in Mangbang-Longling Area of Western Yunnan, China - Xing-Wang Chang; Mo Xu; Liang-Wen Jiang; Xiao Li; Yun-Hui Zhang (Journal of Chemistry)
Numerous low-temperature geothermal waters are distributed extensively in Mangbang-Longling of western Yunnan in China, whose formation mechanism has not been completely investigated yet. This study focused on the hydrogeochemical evolution, reservoir temperature, and recharge origin of geothermal waters using hydrogeochemical and deuterium-oxygen (D-O) isotopic studies. The low-temperature geothermal waters were characterized by HCO3-Na type, while shallow cold spring was of the hydrochemical type of HCO3-Ca. The hydrogeochemical characteristics of low-temperature geothermal waters were mainly determined by the dissolution of silicate minerals based on the geological condition and correlations of major and minor ions. The reservoir temperatures of low-temperature geothermal waters ranged from 111°C to 126°C estimated by silica geothermometry and the silicon-enthalpy graphic method. Low-temperature geothermal waters circulated at the largest depth of 1794–2077 m where deep high-temperature geothermal waters were involved. The data points of δD and δ18O of the hot spring water samples in the study area show a linear right-up trend, indicating the δ18O reaction between the water and rock and a possible mixture of magmatic water from below. The low-temperature thermal waters were recharged by meteoric water at the elevation of 2362–3653 m calculated by δD values. Upwelling by heating energy, low-temperature geothermal waters were exposed as geothermal springs in the fault and fracture intersection and mixed by up to 72% shallow cold waters at surface. Based on acquired data, a conceptual model of the low-temperature geothermal waters in the Mangbang-Longling area was proposed for future exploitation.